Improved order management and delivery of medicines of pharmaceuticals in context of rural Bangladesh - Al-Amran, Khaleed; Rahman, Saidur; Shafi, Ali Al Asadullah Mohammad (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.